Embodiment and inspiration of Chinese philosophy of life in traditional music education - Jian Hu (Trans/Form/Ação)
This paper discusses the embodiment of Chinese life philosophy in Chinese traditional music education and emphasizes its important enlightenment to traditional music education. The innovation point lies in the in-depth study of the lack of reflection on Chinese philosophy of life in traditional music education. It puts forward how to integrate the principles of life philosophy, such as “harmony, Qi and imagery”, into the specific process of music education. The specific process includes discussing the basic concepts of music education in ancient China and exploring the application of life philosophy to music aesthetics. Through the philosophical embodiment of Chinese life philosophy, such as “harmony between heaven and man” and interactive trauma, this paper emphasizes the philosophical aspects of traditional music education, as well as the “harmony” and “imagery” in music aesthetics. Finally, this paper summarizes the importance of life philosophy in Chinese traditional music education, and discusses its potential value and enlightenment to traditional music education.